Time-dependent impact of immunosuppressant regimens on cardiovascular outcomes in kidney transplant recipients: a nationwide cohort study - Jinhyun Park; Wonhui Choi; Jinseub Hwang; Young-Mi Ah; Byung Ha Chung; Yun-Kyoung Song (Frontiers in Pharmacology)
ObjectivesWe aimed to evaluate the effect of different immunosuppressive regimens on the risk of major adverse cardiovascular events (MACEs) in kidney transplant recipients (KTRs).MethodsThis retrospective cohort study used nationwide claims data from the Korean Health Insurance Review and Assessment Service from between 2010 and 2021. Immunosuppressive medications were analyzed as time-dependent variables, and the primary outcome was MACEs, defined as a composite of myocardial infarction, coronary revascularization, ischemic stroke, and all-cause mortality.ResultsA total of 8,056 KTRs were included in the analysis, with significant risk factors for MACEs identified as male sex, older age, longer dialysis duration, lower economic status, and greater comorbidity. At the time of the kidney transplant, 86.7% of the KTRs were administered standard triple therapy, after which various immunosuppressive regimens, including sirolimus-inclusive regimens, were employed. The risk of MACE was lower or comparable in KTRs standard triple therapy than in those receiving most other immunosuppressive regimens. However, corticosteroid withdrawal was associated with a significant reduction in cardiovascular risk, particularly in KTRs with preexisting diabetes or dyslipidemia.ConclusionThese findings suggest that early consideration should be given to minimizing steroid use in KTRs with dyslipidemia or diabetes to optimize cardiovascular outcomes.